Cytotoxicity of ((E)-1-(4-aminophenyl)-3-phenylprop-2-en-1-one)) on HeLa cell line - Adisty Ridha Damasuri; Eti Nurwening Sholikhah; Mustofa (Indonesian Journal of Pharmacology and Therapy, 2020)
In our previous study, some amino chalcone derivatives have been synthesized and evaluated their cytotoxicity against breast cancer cell line T47D. Among 11 amino chalcone derivatives, ((E)-1-(4-aminophenyl)-3-phenylprop-2-en-1-one)) exhibited the most active compound.This study aimed to investigate cytotoxic activity of the ((E)-1-(4-aminophenyl)-3-phenylprop-2-en-1-one)) against cervical cell line (HeLa). The cytotoxic activitywas determined using the MTT colorimetric assay. Cisplatin was used as positive control. From this MTT method, inhibitory concentration 50% (IC50) values were determined by probit analysis based on the relationship between log concentrations versus the percentage of cells growth inhibition.The results showed that the IC50 of ((E)-1-(4-aminophenyl)-3-phenylprop-2-en-1-one)) and cisplatinwere 22.75 ± 19.13 μg/mL and 14.96±1.08 μg/mL, respectively. In conclusion, the ((E)-1-(4-aminophenyl)-3-phenylprop-2-en-1-one)) has moderate cytotoxic activity against HeLa cell line based on National Cancer Institute (NCI) criteria.